Live birth following serial vitrification of embryos and PGD for fragile X syndrome in a patient with the premutation and decreased ovarian reserve - Nayot, Dan (Springer US, 2013)
PURPOSE: To present a live birth resulting from serial vitrification of embryos and pre-implantation genetic diagnosis (PGD). METHODS: A 31-year-old with primary infertility, fragile-X premutation, and decreased ovarian reserve (DOR) (baseline FSH level 33 IU/L), presented after failing to stimulate to follicle diameters >10 mm with three cycles of invitro fertilization (IVF). After counseling, the couple opted for serial in-vitro maturation (IVM), embryo vitrification, and genetic testing using array comparative genomic hybridization (aCGH) and PGD. Embryos were vitrified 2 days after intra-cytoplasmic sperm injection (ICSI). Thawed embryos were biopsied on day-three and transferred on day-five. RESULTS: The couple underwent 20 cycles of assisted reproductive technology. A total of 23 in-vivo mature and five immature oocytes were retrieved, of which one matured in-vitro. Of 24 embryos, 17/24 (71 %) developed to day two and 11/24 (46 %) survived to blastocyst stage with a biopsy result available. Four blastocysts had normal PGD and aCGH results. Both single embryo transfers resulted in a successful implantation, one a blighted ovum and the other in a live birth. CONCLUSIONS: Young patients with DOR have potential for live birth as long as oocytes can be obtained and embryos created. Serial vitrification may be the mechanism of choice in these patients when PGD is needed.